2013
DOI: 10.1063/1.4812035
|View full text |Cite
|
Sign up to set email alerts
|

Mixing behaviour of cohesive and non-cohesive particle mixtures in a ribbon mixer

Abstract: Abstract. Ribbon mixers are used in a wide range of applications involving pharmaceuticals, ceramics and cosmetics, to name a few. Here, the discrete element method is used to investigate the effect of impeller speed on the mixing behaviours of cohesive as well as non-cohesive particle mixtures in a ribbon mixer, which has a horizontal cylindrical vessel. The mixing behaviours are characterized by particle-scale and macroscopic mixing indexes. Simulations show that the mixing rate increases with the impeller s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Since an excessive or insufficient dose of a pharmaceutical could have severe health consequences, thorough particle mixing is crucial [1]. This mixing may by conducted as a continuous process, such as in many food production applications, or as a batch process [2][3][4]. Batch mixers are commonly found in particle mixing for pharmaceutical goods, where they are more suited to the regulations placed upon the manufacture of such goods [5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since an excessive or insufficient dose of a pharmaceutical could have severe health consequences, thorough particle mixing is crucial [1]. This mixing may by conducted as a continuous process, such as in many food production applications, or as a batch process [2][3][4]. Batch mixers are commonly found in particle mixing for pharmaceutical goods, where they are more suited to the regulations placed upon the manufacture of such goods [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fill level is of great interest in particle mixing due to the throughput maximisation problem that arises by balancing the short mixing time and small volumes of low fill levels with the long mixing time and large volume of high fill levels [6]. DEM Simulation studies by Halidan et al [2,3] focus on the effect of cohesiveness in particles when being mixed in ribbon mixers. Their work showed that cohesiveness, characterised by the Bond number, decreased the rate of mixing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations